2022
DOI: 10.3390/ani12202757
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Factors for Accelerating the Transition to Animal-Testing-Free Medical Science through Co-Creative, Interdisciplinary Learning between Students and Teachers

Abstract: Even with the introduction of the replacement, reduction, refinement (the three Rs) approach and promising technological developments in animal-testing-free alternatives over the past two decades, a significant number of animal tests are still performed in medical science today. This article analyses which factors could accelerate the transition to animal-free medical science, applying the multi-level perspective (MLP) framework. The analysis was based on qualitative research, including a desk study (literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…This suggests that there are some students who are aware that the transition regards society as a whole and are willing to contribute to it with different expertise. Whilst education on particular animal-free techniques is currently available in some curricula, our participants and other studies report that it is not mandatory [15]. Furthermore, universities still lack courses that focus on developing critical skills regarding the positioning of animal-free innovations and experimental design.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This suggests that there are some students who are aware that the transition regards society as a whole and are willing to contribute to it with different expertise. Whilst education on particular animal-free techniques is currently available in some curricula, our participants and other studies report that it is not mandatory [15]. Furthermore, universities still lack courses that focus on developing critical skills regarding the positioning of animal-free innovations and experimental design.…”
Section: Discussionmentioning
confidence: 92%
“…Recent research [15,16] has mapped current barriers to the implementation of animalfree methods, delivering a complex landscape of governmental, regulatory, and societal roadblocks that need to be addressed to facilitate the transition. Inadequate funding for non-animal research, lack of data sharing among research institutions, and outdated regulatory requirements are often identified as important constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More openness in exchanging information between colleague researchers is considered the most critical factor for better use of 3Rs knowledge [11]. To accelerate the efforts to disseminate 3Rs approaches accordingly, transition science may be a feasible route to disclose how all stakeholders (e.g., funders, institutions that accommodate animal experiments, researchers, and legislators) can interact to achieve this [32,33]. Transitions can be seen as a development from a current regime to a new, desired, more-sustainable regime, e.g., transition science on replacement aims to understand how to govern the shift towards phasing in new animal-free methods and how to phase out animal testing in the current system.…”
Section: Fast-forwarding 3rs Implementation-a Shared Responsibilitymentioning
confidence: 99%
“…This status quo is backed by regulations, industry norms, and practices. "The landscape level" represents society at large, where societal values, attitudes of regulators, economics, academia, and technical advancements shape both the regime and niche levels [32,33]. It may even be that new alternatives putting an additional workload on researchers themselves may become apparent.…”
Section: Fast-forwarding 3rs Implementation-a Shared Responsibilitymentioning
confidence: 99%